Diseño De E-Actividades Basadas En El Mobile Learning Para La Interacción De Clases Síncronas En La Asignatura De Informática Para Primero De Bachillerato De La Unidad Educativa Mariscal Sucre Alausí-Achupallas - Tixi Saigua, Ana Elizabeth (2023)
ABSTRACT: Currently, technology advances with leaps and bounds, which is why educational institutions challenge the change in the methodology of the teaching-learning process with the new modality of study, virtuality, where Mobile Learning is defined as mobile learning through which The teacher can make use of this methodology in the classroom for a synchronous class through the use of a cell phone, thus facilitating the development of skills and abilities in the student. The study's objective was to design e-activities based on Mobile learning for the interaction in synchronous classes of the subject of computer science in the first year of high school students of the Mariscal Sucre Educational Unit. The methodology used was quantitative. The sample consisted of 50 students. The survey was applied as a technique of closed questions according to the Likert scale. As a result, it was found that teachers needed to use technological tools to teach. Through this study, it was possible to conclude, among the topics investigated, that M-learning offers new methods of education where technologies support teaching, which allows instructors and students to be physically separated, favoring a set of possibilities associated with new mobile technologies and wireless communication networks, generating a greater degree of mobility and flexibility either by the student or by the teacher.